Clinical and economic impact of extracardiac lesions on coronary CT angiography. Issue 18 (22nd March 2022) - Kelion, Andrew; Sabharwal, Nikant; Holdsworth, David; Dawkins, Sam; Peschl, Heiko; Sykes, Anny; Bashir, Yaver
Abstract : Objective: When reporting coronary CT angiography (CCTA), extracardiac structures are routinely assessed, usually on a wide field-of-view (FOV) reconstruction. We performed a retrospective observational cross-sectional study to investigate the impact of incidental extracardiac abnormalities on resource utilisation and treatment, and cost-effectiveness. Methods: All patients undergoing CCTA at a single institution between January 2012 and March 2020 were identified. The indication for CCTA was chest pain or dyspnoea in >90%. Patients with ≥1 significant extracardiac findings were selected. Clinical follow-up, investigations and treatment were documented, and costs were calculated. Results: 4340 patients underwent CCTA; 717 extracardiac abnormalities were identified in 687 individuals (15.8%; age 62±12 years; male 336, 49%). The abnormality was already known in 162 (23.6%). Lung nodules and cysts were the most common abnormalities (296, 43.1%). Clinical and/or imaging follow-up was pursued in 292 patients (42.5%). Treatment was required by 14 patients (0.3% of the entire population), including lung resection for adenocarcinoma in six (0.1%). All but two abnormalities (both adenocarcinomas) were identifiable on the limited cardiac FOV. The cost of reporting (£20) and follow-up (£33) of extracardiac abnormalities was £53 per patient. The cost per discounted quality-adjusted life year was £23 930, increasing to £46 674 for reporting the wide FOV rather than the cardiac FOV alone. Conclusions: Extracardiac abnormalities are common on CCTA, but identification and follow-up are costly. The few requiring treatment are usually identifiable without review of the wide FOV. The way in which CCTAs are scrutinised for extracardiac abnormalities in a resource-limited healthcare system should be questioned.